Analisis Dampak Lalulintas Terhadap Pembangunan (Stasiun Pengisian Bahan Bakar Umum) SPBU Di Ruas Jalan Poros Bulukumba-Bira - Muhammad Nurhidayat; Fathurrahman Burhanuddin (LOSARI Jurnal Arsitektur, Kota dan Permukiman, 2020)
Changes in land use, both changes in category and intensity, will generate traffic so that small or large will have an influence on the surrounding traffic. As a result of the construction of this gas station, of course, will cause changes in the circulation pattern of vehicles at the location of the gas station construction. In order to anticipate the occurrence of significant traffic impacts on the transportation network in the vicinity of the development, it is necessary to conduct a traffic impact analysis. Traffic impact analysis or often called Andalalin is a special study that assesses the effects caused by traffic generated by an area development on the surrounding transportation network. This study aims 1. To examine the impact of the construction of the Bulukumba-Bira gas station on the surrounding traffic conditions; 2. Assessing the form of improvement or improvement needed to accommodate changes that occur as a result of new developments; 3. Assessing the suitability of land use with traffic conditions, the number and location of access, as well as alternative treatments for changes in traffic conditions around the location of the gas station construction.